Role of neuromedin B in the control of the release of thyrotropin in the rat. - Rettori, V (1989)
Neuromedin B (NB), a bombesin-like peptide, was first isolated from porcine spinal cord and subsequently found in the central nervous systems of rat, cat, and human. Immunocytochemical studies have shown that NB is present in hypothalamus and various other regions of the brain and in thyrotrophs of the anterior pituitary of the rat. The possible physiological role of NB in the hypothalamic-pituitary axis is not known. Therefore, we studied the in vivo effect of this peptide on the plasma levels of thyrotropin (TSH) after administering NB to conscious freely moving adult male rats. When injected i.v., only the highest dose of NB (50 micrograms, 44.2 nmol) significantly lowered plasma TSH levels relative to levels in saline controls. When injected intraventricularly, NB doses of 0.5 and 5 micrograms (0.44 and 4.42 nmol, respectively) lowered plasma TSH levels with a 15-min latency period. Responsiveness of the pituitary to TSH-releasing hormone (TRH) was tested after the effective dose of NB was administered i.v. The increase in plasma TSH levels after the i.v. injection of 1 microgram of TRH was not altered by NB. NB at 10(-9) to 10(-7) M also reduced TSH release from hemipituitaries incubated in vitro without decreasing the response to TRH. Consequently, NB appears to have a direct inhibitory effect on TSH release from thyrotrophs. Since the response to TRH was not depressed, NB appears to act on a separate NB thyrotroph receptor that suppresses TSH release by a TRH-independent mechanism. After antiserum directed against NB was injected into the third ventricle, there was a highly significant elevation of the plasma level of TSH, beginning at 4 hr and increasing at 6 hr, relative to initial levels and levels in normal rabbit serum-injected controls. These results indicate that NB has a tonic suppressive effect on TSH release and is a physiologically significant TSH-release-inhibitory factor.